Studies on Adriaphaenops Noesske with the description of five new species from the Dinarides (Coleoptera: Carabidae: Trechini) - Lohaj, Roman; Lakota, Ján; Quéinnec, Eric; Pavićević, Dragan; Čeplík, Dávid (Zootaxa, 2016)
The species belonging to the trechine genus Adriaphaenops Noesske, 1928 are studied. As a result, seven currently known and five newly described species are recognized. Morphological characters of the habitus (especially the shape of head and pronotum) as well as male genitalia are widely used to delimit the species. The following new species are described: A. albanicus sp. nov. (Albania, Shkodër, Boga, Thatë Mts.), A. jasminkoi sp. nov. (Bosnia & Hercegovina, Nevesinje, Novakova pećina cave), A. mlejneki sp. nov. (Montenegro, Gornje Stravče, Kučke planine Mts.), A. njegosiensis sp. nov. (Montenegro, Cetinje, Cetinjska pećina cave) and A.rumijaensis sp. nov. (Montenegro, Virpazar, Rumija Mts.). Lectotype for A. stirni (Pretner, 1959) is designated. Data on the distribution and ecology of new taxa, complemented with descriptions of the type localities are provided. Key to the identification of all twelve Adriaphaenops species, as well as a key of all hitherto known aphaenopsoid Trechini genera from Dinarides are also given.